Exterior Facades with a Neo Vernacular Architecture Approach to the Seni Bela Diri Pencak Silat Competition and Training Building in Madiun Regency - Dian Ayu Kusumawati; Failasuf Herman Hendra; Firdha Ayu Atika (Journal of Civil Engineering, Planning and Design, 2023)
Madiun Regency is an area of martial arts preservation of Pencak silat. Thus, Madiun Regency has several pencak silat hermitages as a forum for learning pencak silat martial arts but currently does not have a representative pencak silat facility as a joint competition and training event. Therefore, designing a Pencak Silat Martial Arts Competition and Training Building with a Neo Vernacular Architecture theme approach derived from local culture is necessary. This is in connection with the aim of the Madiun Regency government to have a plan to provide a Joint Silat College Building to unite martial arts colleges and improve the economy in Madiun Regency. The design research method uses qualitative methods in case studies and descriptive, data collection techniques in the form of observation, literature studies, case studies, documentation, questionnaires, and interviews. The Neo Vernacular Architecture Theme approach applied to the shape aspect is expected to be able to combine local culture with the current architectural style. The design of the Pencak Silat Martial Arts Competition and Training Building with the Neo Vernacular architectural theme uses the macro concept of cultural stylization and the micro concept of cultural representation which is expected to represent the formation of the Joglo House and the characteristics of the Pencak silat building. the facade design represents pencak silat techniques/attitudes which apply the form of Sembong cloth attributes as an ornament and uses the colors yellow, green, and brown.